Adaptive Modulationsverfahren für die schmalbandige Powerline-Kommunikation in Niederspannungsnetzen - Kaiser, Cornelius (Forschungsberichte aus der Industriellen Informationstechnik, 2020)
Powerline communications utilize the existing energy distribution network for information transmission. In this work, the low voltage grid is investigated as a transmission channel for frequencies up to 500 kHz. Based on characterizing the channel with regard to its cyclostationary properties, novel adaptive transmission methods are developed. The presented methods are evaluated under realistic channel conditions.